Accuracy of the evaluation of forest areas based on Landsat data using free software - Zając, Paulina; Dębińska, Ewa; Maciuk, Kamil (Folia Forestalia Polonica, 2023)
Ever-evolving technologies are enabling us to obtain information about the world around us ever more quickly and precisely. This state of affairs contributes to the growing need to store and analyse data. For today’s scientists, this is a challenge because it involves analyses on a global scale. This also applies to spatial data, vast amounts of which are made available online. The Google Earth Engine platform is such a place on the web. It is not just a catalogue for browsing, but above all an environment for programming useful applications. Among free software, it is difficult to find one that is not dependent on the parameters of the computer. In the case of Google Earth Engine, the processes programmed by the user are executed on powerful external servers, and the user only gets the finished result, which he can download to his computer and use in further work. The initial chapters introduce the basic concepts and characterise the specifics of working in this environment, taking into account the limitations of the platform. Then, the individual stages of the algorithm developed by the authors are described, trying to explain well the reasons for the use of particular methods and functions. In order to verify the correctness of the obtained results, existing databases on the subject and published research results of other authors were used.